Experimental investigation on mechanical properties of Epoxy/graphene/fish scale and fermented spinach hybrid bio composite by hand lay-up technique. (2021) - Yogeshwaran, S.; Natrayan, L.; Rajaraman, S.; Parthasarathi, S.; Nestro, S.
Abstract: Composites which made up of fiber reinforcements are universally endorsed option for the automobiles with a lightweight. Due to the unique properties of fiber-reinforced composites, it became a perfect alternative for traditionally used materials. Most of the automobile industries prefer polymer matrix fiber-reinforced composites for the reason that its light weight helps in carbon emission reduction. Recently graphene has attracted both academic and industrial interest because it can produce a dramatic improvement in properties at very low filler content. In this research, Bio wastes such as fish scale and fermented spinach used as reinforcement with epoxy resin and graphene powder fabricated by using hand layup technique. Mechanical properties such as tensile, flexural and impact strength were investigated at room temperature. Results exposed that Epoxy/graphene/fish scale/fermented spinach composite (Sample 3) showed better mechanical properties compare to then Epoxy/graphene/fish scale (Sample 1) and Epoxy/graphene/ fermented spinach composites (Sample 2).